2010
DOI: 10.7183/0002-7316.75.3.627
|View full text |Cite
|
Sign up to set email alerts
|

“Men, Women, and Children Starving”: Archaeology of the Donner Family Camp

Abstract: In spring of 1846, the George and Jacob Donner families and some 80 traveling companions began their overland trek to California. When the party ascended the Sierra Nevada in late October, a snowstorm forced the group to bivouac. At this point, the train became separated into two contingents; the larger party camped near Donner Lake and the smaller group—including the Donner families—settled at Alder Creek. Though written accounts from the Lake site imply many resorted to cannibalism, no such records e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
17
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 76 publications
0
17
0
Order By: Relevance
“…Pot polish is characterised by abrasion/polishing to projecting ends of bone because of contact with the walls of a cooking vessel (White, : 120‐124). Pot polish has been produced experimentally by heating bone fragments devoid of soft tissue in water in metal or ceramic vessels (White, : 121‐122; Dixon et al ., ; Kopp & Graham, ). Archaeologically, it has been observed in animal bones which have been processed to extract bone grease (Dixon et al ., ), and in human remains in suspected cases of cannibalism (White, ; Turner & Turner, ; Cáceres et al ., ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pot polish is characterised by abrasion/polishing to projecting ends of bone because of contact with the walls of a cooking vessel (White, : 120‐124). Pot polish has been produced experimentally by heating bone fragments devoid of soft tissue in water in metal or ceramic vessels (White, : 121‐122; Dixon et al ., ; Kopp & Graham, ). Archaeologically, it has been observed in animal bones which have been processed to extract bone grease (Dixon et al ., ), and in human remains in suspected cases of cannibalism (White, ; Turner & Turner, ; Cáceres et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…Cannibalism in the Franklin Expedition or ceramic vessels (White, 1992: 121-122;Dixon et al, 2010;Kopp & Graham, 2011). Archaeologically, it has been observed in animal bones which have been processed to extract bone grease (Dixon et al, 2010), and in human remains in suspected cases of cannibalism (White, 1992;Turner & Turner, 1995;Cáceres et al, 2007). Pot polish has been most often reported on long-bone fragments, but has also been seen on other elements (White, 1992;Turner & Turner, 1999).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The well-known historic Alferd Packer case of murder and short-term survival cannibalism involved only five victims, for example (Rautman and Fenton 2005). And while the Donner Party tragedy involved the cannibalization of 21 individuals in total, these may be thought of as a series of discrete incidents involving a handful of individuals at a time and occurring in six separate locations-Alder Creek (n = 5), Camp of Death (n = 4), Sierra foothills (n = 3), Murphy Cabin (n = 2), Breen Cabin (n = 4), and Starved Camp (n = 3)-over a number of months (Dixon et al, 2010;Grayson, 1990;Hardesty, 1997).…”
Section: Starvation Cannibalismmentioning
confidence: 99%
“…From the mechanics point of view, modelling results demonstrated a significant impact of material properties of cement lines on microcrack-osteon interactions [74,99]. Quantitative analyses of cortical bone have also reported that the size and density of osteons vary with age [78,[100][101][102][103][104]. Because cement lines are prime sites for microcrack formation, an increase in the osteon density could lead to a higher microcrack density, which could reduce the crack-initiation toughness [32,34].…”
Section: Bone Toughening Mechanismsmentioning
confidence: 99%